2022
DOI: 10.3390/educsci12110813
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of Online Education during COVID-19 Lockdowns: Direct and Indirect Effects on Learning

Abstract: The COVID-19 pandemic forced an abrupt transition to fully online learning in universities that typically provided campus-based teaching. We examined the learning experience of undergraduate and postgraduate students during this transition at a UK university. Qualitative surveys and interview responses revealed both direct effects of the transition to online learning and indirect effects caused by the COVID-19 induced lockdown. Direct effects related to interaction and communication altered study-related oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
5
0
2
Order By: Relevance
“…The most common response to this question, as shown in Table 7, was that online classes created challenges in forming and maintaining peer relationships. This finding suggests that friendly and cooperative relationships with other students are an essential part of developing a sense of belonging in engineering and missing these connections can be an important factor in a lack of connection with a student's major [9,10,50]. These findings may be especially related to this cohort of students, many of whom have never met their peers in person at the time of this study.…”
Section: Insights On Student Experiences In the Context Of The Univer...mentioning
confidence: 89%
“…The most common response to this question, as shown in Table 7, was that online classes created challenges in forming and maintaining peer relationships. This finding suggests that friendly and cooperative relationships with other students are an essential part of developing a sense of belonging in engineering and missing these connections can be an important factor in a lack of connection with a student's major [9,10,50]. These findings may be especially related to this cohort of students, many of whom have never met their peers in person at the time of this study.…”
Section: Insights On Student Experiences In the Context Of The Univer...mentioning
confidence: 89%
“…Over the same period, a quantitative survey by Karada g et al [53] of 30 universities in Turkey found similar problems of low student engagement but noted fewer issues in universities with developed distance education capacities. In a smaller-scale qualitative study of UK student perceptions during the pandemic conducted by Dinu et al [54], there were positive as well as negative views. Some students saw greater opportunities in online working, but others found significant challenges; however, all students welcomed the greater flexibility of online study.…”
Section: Factor E: Growth In Online Education and Trace Data Of Stude...mentioning
confidence: 99%
“…Hal tersebut membuktikan bahwa kesiapan dosen/ staf pendidik, staf kependidikan, dan mahasiswa secara menyeluruh perlu diantisipasi. 13,14 Dinu et al 15 melaporkan efek langsung dan tidak langsung pada pembelajaran daring memiliki kesamaan dengan di FKUPH dalam interaksi belajar dengan peer group. Kebutuhan belajar bersama menjadi terhambat dengan PPKM dan pelaksanaan daring.…”
Section: Diskusiunclassified
“…Beberapa responden di FKUPH merasa nyaman walaupun belajar sendiri karena lebih menyukai ketenangan sehingga dapat lebih berkonsentrasi. 15 Hilangnya interaksi dengan pasien menjadi keluhan responden dari Polandia. Responden di FKUPH juga menyatakan bahwa sebagai dokter perlu berinteraksi langsung dengan pasien, sehingga pembelajaran keterampilan klinis secara daring tanpa pasien simulasi menjadi kurang efektif.…”
Section: Diskusiunclassified